(3OjhGf GdbWGejs - (3GdbWGej , YejQ Hf Tjje Hf YeQh Hf YHGO GdJZdHj, CHh SYjO,J (B130 (3g` s ((3CHhGdHQcGJ GdeHGQc Hf CHj GdaJM Hf GdeHGQc Hf ehghHHf ZGdH s)
(3ChdgG (B:s
(3bGd CHhYeQ hjbGd GdbWGej(B: (3hEfeG bWeg bhdg(B: (3ojMqWogqf LGfHkG aLGfHG MW GdbWGeqj GdbWG GdbhGQHG s
(3BNQgG (B:s
(3de JrOQ eG ehSi hdG SWGegG jbGd(B: (3CSWehG Scjfce(B: (3Cj CMOhgG Ke TYQ GdbWGej s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B264s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B181 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B806s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3BOGH (B546) s
Keywords: (3GdCOHs